The Effect of Moringa oleifera Extract as Candidate Prebiotic to Increase the Growth of Lactobacillus acidophilus and Lactobacillus plantarum Probiotics - Widya Paramita Lokapirnasari (Journal of Global Pharma Technology, 2020)
Objectives: The potential of probiotics can be increased by adding prebiotics, which are substances that cannot be digested, but can be used by probiotics to increase their growth. Prebiotics generally consist of oligosaccharides. Moringa oleifera has potential as a prebiotic candidate. This study aims to prove the use of Moringa oleifera (M. oleifera) extract as a prebiotic candidate to increase the growth of Lactobacillus acidophilus (L. acidophilus) and Lactobacillus plantarum (L. plantarum) probiotics. Methods: This study consisted of 4 treatments and each treatment was repeated 5 times. The treatments consisted of: P0: 0% Moringa oleifera extract, P1: 0.1% Moringa oleifera extract (v/v), P2: 0.2% M. oleifera extract (v/v), P3: 0.3% M. oleifera extracts (v/v). The probiotic concentration is 1.5x108CFU/ml. Results: The results showed that there was a significant difference (p